Improving Students’ Ability In Reading Narrative Text By Using Reading Aloud And Question And Answer Technique At Smp Negeri 1 Langowan - Tini Mogea (Jurnal Pendidikan dan Sastra Inggris, 2023)
This research is intended to prove whether reading aloud and the question-and-answer technique are effective or not in improving students’ ability to read narrative text at SMP Negeri 1 Langowan. This research is classified as "classroom action research" because it was conducted in a cycle. The second-grade students were taken as a sample consisting of 19 students. The writer used a reflective journal, field notes, and tests in collecting data. The data were analyzed through the "triangulation" method. It is a qualitative data analysis technique in which related data are compared and evaluated to explain the parallel characteristics. The result shows that by applying reading aloud in Cycle 1, it was found that only 36.84 percent, or 7 students, of the 19 students could understand the text given with some comprehension, and it was categorized as unsatisfactory. By the application of question and answer in Cycle 2, it shows 52.63 percent of students, or 10 students, made progress in the teaching-learning process of reading ability development, and it was categorized as quite satisfying. In Cycle 3, the majority of students made great progress, with 68.42 percent or 12 students making great progress, and it was categorized as satisfying.